Palaeoglaciation in the Low Latitude, Low Elevation Tropical Andes, Northern Peru - Lee, Ethan; Ross, Neil; Henderson, Andrew C. G.; Russell, Andrew J.; Jamieson, Stewart S. R.; Fabel, Derek (Frontiers in Earth Science, 2022)
Characterising glaciological change within the tropical Andes is important because tropical glaciers are sensitive to climate change. Our understanding of glacier dynamics and how tropical glaciers respond to global climate perturbations is poorly constrained. Studies of past glaciation in the tropical Andes have focused on locations where glaciers are still present or recently vacated cirques at high elevations. Few studies focused on lower elevation localities because it was assumed glaciers did not exist or were not as extensive. We present the first geomorphological evidence for past glaciations of the Lagunas de Las Huaringas, northern Peru, at elevations of 3,900–2,600 m a.s.l. Mapping was conducted using remotely-sensed optical imagery and a newly created high-resolution (∼2.5 m) digital elevation model (DEM). The area has abundant evidence for glaciation, including moraines, glacial cirques, hummocky terrain, glacial lineations and ice-sculpted bedrock. Two potential models for glaciation are hypothesised: 1) plateau-fed ice cap, or 2) valley glaciation. Assuming glaciers reached their maximum extent during the Local Last Glacial Maximum (LLGM), between 23.5 ± 0.5 and 21.2 ± 0.8 ka, the maximum reconstructed glacial area was 75.6 km2. A mean equilibrium line altitude (ELA) of 3,422 ± 30 m was calculated, indicating an ELA change of −1,178 ± 10 m compared to modern snowline elevation. There is an east to west ELA elevation gradient, lower in the east and higher in the west, in-line with modern day transfer of moisture. Applying lapse rates between 5.5 and 7.5°C/km provides a LLGM temperature cooling of between 6.5–8.8°C compared to present. These values are comparable to upper estimates from other studies within the northern tropical Andes and from ice-core reconstructions. The mapping of glacial geomorphology within the Lagunas de las Huaringas, evidences, for the first time, extensive glaciation in a low elevation region of northern Peru, with implications for our understanding of past climate in the sub-tropics. Observations and reconstructions support a valley, rather than ice cap glaciation. Further work is required to constrain the timing of glaciations, with evidence of moraines younger than the LLGM up-valley of maximum glacier extents. Numerical modelling will also enable an understanding of the controls of glaciation within the region.